Revealing phase-specific properties of elastomeric blends and their molecular structure at the nanoscale by AFM. (4th October 2022) - Cosas Fernandes, João Paulo; Federico, Carlos Eloy; Basterra-Beroiz, Beatriz; Weydert, Marc; Quintana, Robert
Abstract: Immiscible elastomeric blends are of interest for a variety of technical applications, in which the optimization of material properties and performance are influenced by the result of co-vulcanization. The differential solubility of curing additives used during the vulcanization process, such as sulfur or accelerators, can lead to different concentrations and vulcanization rates in each elastomer depending on their composition. Therefore, the comprehension of the phase-specific effects of curatives in the blend is desirable. In this work, two different atomic force microscopy (AFM) approaches are explored: Amplitude Modulated – Frequency Modulated (AM-FM) and AFM-IR, for the characterization of the phase-specific nanomechanical properties and molecular structure, respectively. These methods are applied to the analysis of polyisoprene/polybutadiene (PI/BR) blends, focusing on the study of the effects of a conventional and an efficient vulcanization system. AFM-IR mappings at the nanoscale provide images of the morphology based on the molecular structure of the phases and complementary information on the effects of the variation of the sulfur/accelerator ratio through the observation of changes of the trans / cis ratio at the nanoscale. The variations of viscoelastic properties revealed by quantitative nanomechanical mappings are associated with the cross-link density evolution in the samples as a function of variation of curatives in the compound and are observed to follow the same trend as molecular structure changes observed by AFM-IR. Graphical abstract: Image 1 Highlights: An AFM method to obtain with more confidence crosslink density data in rubber blends. Quantitative AFM correlates crosslink density evolution with variations of curatives. AFM-IR correlates curing additives with structural changes in the blend system. Merging mechanical and chemical AFM mappings boosts vulcanization understanding.